Diversity of Innovation Interpretation: Case Studies of Innovative Solutions in Seaports - Adrianna KARAS (Communications of International Proceedings, 2021)
Increased use of technology and implementation of innovative solutions are part of the strategy of seaports and maritime transport. The Covid-19 pandemic has revealed that the maritime sector has become unstable and at the same time a trend of increased concentration to technological development has developed through the pandemic. The maritime industry increasingly implements various types of technological solutions as well as non-technological describing them as innovation, although the concept of innovation is not clearly interpreted and has many descriptions. The article reviews the definition of innovation, which shows the discrepancy in the understanding of this concept, despite the fact that the definitions of innovation contain certain fixed elements, referring to e.g. Schumpeter's theory. The next part of the article analyzes examples of modern technologies in European seaports called innovations and are in line with global trends.
Keywords: Innovation; Seaports; New Technologies; Digitalization